Accessibility Challenges of Using Podcasts and Vodcasts in a South African Distance Learning University - Mohale, Ntshimane Elphas (Research in Social Sciences and Technology, 2024)
Academic writing presents a range of challenges for students, particularly those enrolled in distance university institutions. These challenges encompass various facets such as understanding citation and referencing, developing a distinctive writer’s voice, mastering academic discourse, paraphrasing, summarising, and adhering to academic conventions. Notably, deficiencies in academic writing skills often trace back to inadequate preparation during high school education, potentially leading to qualification deferment and high dropout rates. To tackle these challenges, podcasts and vodcasts emerged as essential tools to bridge academic gaps, catering to diverse learning styles and offering flexibility beyond traditional teaching methods. However, the efficacy of supplemental multimedia tools warrants exploration, considering uncertainties regarding student acceptance. Thus, this study aimed to identify accessibility challenges, to reduce existing barriers and enhance accessibility in open distant institutions. Utilising qualitative research methodologies, including focus group discussions and literature analysis, data collection was conducted. The study drew upon Moore’s theory of transactional distance and Garrison et al.’s community of inquiry framework to create collaborative online interactions and meaningful lecturer-student engagement, culminating in the construction of new knowledge. Findings revealed that students did not encounter accessibility challenges and expressed preference for shorter podcasts and vodcasts. These multimedia formats alleviated boredom, clarified complex concepts, prevented monotony, enhanced attention and comprehension, stimulated interest, facilitated active learning, and accommodated various learning styles. Podcasts and vodcasts reduced transactional distance and created a sense of community. Contrary to prevailing literature, students did not encounter accessibility challenges, shifting the focus towards shorter, high-quality multimedia content rather than accessibility concerns.